PENDEKATAN RASIONAL-RELIGIUS DALAM PENDIDIKAN ISLAM - Nur Sahed; Eko Sumadi; Suheri Sahputra Rangkuti (Tarbawiyah Jurnal Ilmiah Pendidikan, 2018)
The orientation of Islamic education is different from the orientation of education in general, because in addition to oriented to the worldly aspect, it is also oriented to the dimensions of ukhrawi. Many cues in the Qur'an that can be used as a spirit for Islamic education to balance and align the two orientations. To read the Qur'anic cues, the author uses a rational-religious approach initiated by Jawwad Rida. This approach is used to read the basic philosophy of Iqra 'or Surah al-'Alaq in presenting a discussion entity different from the previous discussion. This article discusses various issues concerning rational-religious approaches, from the aspect of epistemology to the fundamental themes. The themes discussed in this article include thoughts related to current realities, so this article is expected to contribute to the treasury of Islamic education.